Plant Nanovesicles for Essential Oil Delivery - Mónica Zuzarte; Carla Vitorino; Lígia Salgueiro; Henrique Girão (MDPI AG, 2022)
Essential oils' therapeutic potential is highly recognized, with many applications rising due to reported anti-inflammatory, cardioprotective, neuroprotective, anti-aging, and anti-cancer effects. Nevertheless, clinical translation still remains a challenge, mainly due to essential oils' volatility and low water solubility and stability. The present review gathers relevant information and postulates on the potential application of plant nanovesicles to effectively deliver essential oils to target organs. Indeed, plant nanovesicles are emerging as alternatives to mammalian vesicles and synthetic carriers due to their safety, stability, non-toxicity, and low immunogenicity. Moreover, they can be produced on a large scale from various plant parts, enabling an easier, more rapid, and less costly industrial application that could add value to waste products and boost the circular economy. Importantly, the use of plant nanovesicles as delivery platforms could increase essential oils' bioavailability and improve chemical stability while reducing volatility and toxicity issues. Additionally, using targeting strategies, essential oils' selectivity, drug delivery, and efficacy could be improved, ultimately leading to dose reduction and patient compliance. Bearing this in mind, information on current pharmaceutical technologies available to enable distinct routes of administration of loaded vesicles is also discussed.